2022
DOI: 10.1073/pnas.2121499119
|View full text |Cite|
|
Sign up to set email alerts
|

New intranasal and injectable gene therapy for healthy life extension

Abstract: Significance Using CMV as a gene therapy vector we illustrated that CMV can be used therapeutically as a monthly inhaled or intraperitoneally delivered treatment for aging-associated decline. Exogenous telomerase reverse transcriptase or follistatin genes were safely and effectively delivered in a murine model. This treatment significantly improved biomarkers associated with healthy aging, and the mouse lifespan was increased up to 41% without an increased risk of cancer. The impact of this research … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
(63 reference statements)
0
20
0
Order By: Relevance
“…One-time tail vein injection of AAV9-Tert in 1-or 2year-old mice delays the onset of age-related pathologies and extends their lifespans by 24% or 13%, respectively (Bär et al, 2014;Bernardes de Jesus et al, 2012). Moreover, a recent study reported that intranasal or intraperitoneal administration of the mouse cytomegalovirus (MCMV) expressing TERT or FST (follistatin, another target to increase muscle mass and to improve the neuromuscular function) in 18month-old mice once a month for six consecutive months leads to a median lifespan extension of 41.4% or 32.5%, respectively (Jaijyan et al, 2022). Besides shortened telomeres, senescent cells also secrete a group of proinflammatory factors, called SASP, which impair the function of stem cells, alter the organization of the ECM, and spread the senescence phenotype to neighboring cells, leading to systemic chronic inflammation.…”
Section: In Vivo Gene Therapy For Aging Interventionsmentioning
confidence: 99%
“…One-time tail vein injection of AAV9-Tert in 1-or 2year-old mice delays the onset of age-related pathologies and extends their lifespans by 24% or 13%, respectively (Bär et al, 2014;Bernardes de Jesus et al, 2012). Moreover, a recent study reported that intranasal or intraperitoneal administration of the mouse cytomegalovirus (MCMV) expressing TERT or FST (follistatin, another target to increase muscle mass and to improve the neuromuscular function) in 18month-old mice once a month for six consecutive months leads to a median lifespan extension of 41.4% or 32.5%, respectively (Jaijyan et al, 2022). Besides shortened telomeres, senescent cells also secrete a group of proinflammatory factors, called SASP, which impair the function of stem cells, alter the organization of the ECM, and spread the senescence phenotype to neighboring cells, leading to systemic chronic inflammation.…”
Section: In Vivo Gene Therapy For Aging Interventionsmentioning
confidence: 99%
“…An adeno-associated virus serotype 9 (AAV9) encoding telomerase has been shown to extend the lifespan adult/old mice when injected intravenously. Additionally, cytomegalovirus (CMV) encoding telomerase had even more impressive results when administered intranasally and intraperitoneally old mice 37,38 . AAVs are non-replicating vectors, so even slowly-dividing stem cells will eventually lose the vector unless there is some sort of asymmetric inheritance process for the vector genome (even with otherwise symmetrical stem cell division).…”
Section: Two Remaining Issues In the Near Futurementioning
confidence: 99%
“…In translational pursuits, the same group showed that the transient delivery of mRNA encoding TERT rapidly extends telomeres in human cells [ 267 ] and suppresses the hallmarks of progeroid cells [ 268 ]. In a recent study, intranasal and injectable gene therapy has shown promise for healthy life extension in animal models [ 269 ]. Telomerase activation is yet to be clinically tested as a therapeutic approach to CVD prevention and treatment.…”
Section: Perspective On Optimal Clinical Interventionmentioning
confidence: 99%